Diaquadichloridomethylphenyltin(IV)–1,4,7,10,13-pentaoxacyclopentadecane (1/1) - Vafaee, Marzieh (International Union of Crystallography, 2012)
The asymmetric unit of the title cocrystal, [Sn(CH(3))(C(6)H(5))Cl(2)(H(2)O)(2)]·C(10)H(20)O(5), contains two independent formula units. The organotin molecules exhibit a six-coordinate metal atom and are linked to the crown ether molecules by water–crown ether O—H⋯O hydrogen bonds into a linear chain running along [101]. Each coordinated water molecule forms a pair of hydrogen bonds to the same crown ether; for the crown ether molecules, only four of the five O atoms are engaged in hydrogen-bonding interactions. The metal ions show a distorted trans-C(2)SnCl(2)O(2) octahedral coordination geometry [C—Sn—C = 175.3 (1) and 178.9 (1)°].